The Quality of Meat, Carcass, and Cut Yields of Broiler Chicken Fed Diets Containing Purslane Meal Rich in Omega-3 Fats (Jurnal Ilmu dan Teknologi Hasil Ternak, 2023)
This study aims to evaluate the feeding of broilers with ALA-rich purslane supplementation on meat and carcass quality and sensory quality. A total of 180 one-day old, unsexed Cobb broilers were used in this research, and they were divided into 30 pens, with each pen containing 6 birds. Broiler feeding was randomly divided into five treatments based on a basal corn-soybean feed. This study used a completely randomized design (CRD) in one direction with five treatments and five replications. The experimental diets were a basal diet (A0) and basal diets containing 1.5% fish oil and 0% purslane meal (w / w) (A1), 6% (A2), 12% (A3), and 18% (A4). Performance parameter data were recorded and measured over a 35-day period. As many as 30 chickens (n = 6 for each treatment) were slaughtered and processed as carcass and breast meat (Pectoralis Major) samples were collected for meat quality evaluation. The data were analyzed using Analysis of Variance and if there was a significant effect of the treatments then the analysis was continued using Tukey Test. The results showed that adding 12% purslane flour had no a significant effect on carcass weight and cut yields. The diet enriched with purslane flour to a level of 18% for 35 days did not change the water holding capacity (WHC), but it did increase the fat content of the meat. Purslane meal-containing diets reduced cooking losses. The tenderness of the meat produced from chickens fed with purslane meal at a level of 18% (1.93) was higher than those fed purslane meal 12% (1.12). Panelists gave the same perception of preference for meat produced from chickens fed dietary treatments. In conclusion, diets containing purslane meal up to 12% has no negative effect on carcass quality, physicochemical quality and consumer preference for broiler chicken meat.